1998
DOI: 10.1074/jbc.273.9.5385
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the Vesicle Docking Protein p115 Regulates Its Association with the Golgi Membrane

Abstract: The vesicle docking protein p115 was found to be phosphorylated in a cell cycle-specific manner; it was found phosphorylated in interphase but not in mitotic cells. During interphase, however, two forms of p115 were detected in the cells; the phosphorylated form was found exclusively in cytosol, whereas the unphosphorylated form was associated with membranes, mostly of the Golgi complex. The latter form was released from the membranes upon phosphorylation. Mutational analysis revealed that the phosphorylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
66
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 23 publications
1
66
0
Order By: Relevance
“…Phosphorylation of p115 enhances this binding (6), whereas phosphorylation of GM130 inhibits it (7). During mitosis, p115 is dephosphorylated by an unknown phosphatase (8), whereas GM130 is phosphorylated by the mitotic kinase Cdc2 (9). This suggests that the vesiculation of the Golgi apparatus that occurs during cell division may be caused by inhibition of p115 tethering such that Golgi vesicles form but do not dock and fuse (7).…”
mentioning
confidence: 81%
“…Phosphorylation of p115 enhances this binding (6), whereas phosphorylation of GM130 inhibits it (7). During mitosis, p115 is dephosphorylated by an unknown phosphatase (8), whereas GM130 is phosphorylated by the mitotic kinase Cdc2 (9). This suggests that the vesiculation of the Golgi apparatus that occurs during cell division may be caused by inhibition of p115 tethering such that Golgi vesicles form but do not dock and fuse (7).…”
mentioning
confidence: 81%
“…33 Phosphorylated USO1 is found in the cytosol, whereas the unphosphorylated molecule locates on membranes of the Golgi complex and transcytotic vesicles. 34 This study demonstrated interaction between MIF and USO1, as well as colocalization within vesicles of human peripheral blood mononuclear cells (PBMC). Moreover, USO1 was required for the secretion of MIF in response to LPS and was released alongside MIF.…”
Section: Discussionmentioning
confidence: 99%
“…Construction and Transfection of Expression Plasmids-cDNAs encoding the entire coding region of GCP60 (wild type) and B8 were ligated to a position downstream of the sequence encoding the Met-FLAG tag in pSG5 expression vector so that the products could be recognized by the monoclonal anti-FLAG antibody M2 (28,31). The COOH-terminally deleted mutant M1 was prepared by introducing a termination codon into an appropriate site of the wild type plasmid.…”
Section: Methodsmentioning
confidence: 99%
“…The mutant cDNA sequences (D1ϪD3) obtained were verified and ligated in frame to pEGFP-1 for GFP-fused proteins. The plasmid for N-acetylglucosaminyltransferase fused with GFP (NAGFP) (32) (17,31). Cell lysates were prepared and subjected to immunoprecipitation with polyclonal anti-GCP60 as described previously (17,31).…”
Section: Methodsmentioning
confidence: 99%